Teachers' perspectives on formative assessment in physical sciences education - Ramaila, Sam; Mngomezulu, Halalisani; Ramnarain, Umesh; Dhurumraj, Thasmai (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
This study examined teachers' perspectives on the influence of formative assessment on Physical Sciences learners' academic achievement, attitudes, and self-regulation skills. Drawing from qualitative data, the research aimed to understand how formative assessment practices, such as feedback, peer assessments, and self-assessment strategies, shaped learners' engagement and academic outcomes. A purposive sample of 20 Physical Sciences teachers was selected to provide insights into the role formative assessment played in fostering not only academic success but also positive attitudes towards science and enhanced self regulation skills. Through teacher semi-interviews, the study explored how these assessment strategies supported learners' ability to monitor their own progress, adapt their learning approaches, and maintain motivation in a challenging subject area. A thematic analysis was used to analyse the interview data. The findings suggested that formative assessment was a key pedagogical tool that contributed to improved learner performance, more positive attitudes towards Physical Sciences, and the development of essential self-regulation skills. This research had significant implications for the integration of formative assessment into science teaching and learning practices, highlighting its potential to support holistic learner development.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 1, Volume 9, 2025
Keywords: Formative assessment; Learner attitudes; Self-regulation skills; Teacher perspectives; Physics -- Study and teaching; Educational evaluation